2011
DOI: 10.1097/rlu.0b013e3181feeb30
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET/CT Scanning in Charcot Disease

Abstract: presented F-18 FDG PET/CT data may indicate an inflammatory origin of Charcot disease, with secondary bone resorption, possibly due to decreased inhibitory neurogenic inflammatory responses as a result of small fiber neuropathy. If these findings can be confirmed in future studies, F-18 FDG PET/CT scanning may be added to the diagnostic arsenal in Charcot disease, and anti-inflammatory drugs may be added to the therapeutic arsenal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
0
16
0
3
Order By: Relevance
“…Hopfner et al also demonstrated a higher accuracy rate in the detection of osteomyelitis in patients with diabetic Charcot disease compared to MRI ( 41 ). Pickwell et al ( 42 ) have compared the diagnostic power of bone scintigraphy and FDG-PET/CT in the diagnosis of acute CN, and found that FDG-PET/CT was better than the former. In FDG-PET/CT studies, increased uptake within soft tissues rather than bones is a commonly seen feature of CN.…”
Section: Imaging Of Acute Cnmentioning
confidence: 99%
“…Hopfner et al also demonstrated a higher accuracy rate in the detection of osteomyelitis in patients with diabetic Charcot disease compared to MRI ( 41 ). Pickwell et al ( 42 ) have compared the diagnostic power of bone scintigraphy and FDG-PET/CT in the diagnosis of acute CN, and found that FDG-PET/CT was better than the former. In FDG-PET/CT studies, increased uptake within soft tissues rather than bones is a commonly seen feature of CN.…”
Section: Imaging Of Acute Cnmentioning
confidence: 99%
“…и соавт. [31] было показано, что FDG-PET/КТ имеет большую диагностическую ценность для ранней диа-гностики ДНОАП по сравнению с остеосцин-тиграфией.…”
Section: современные возможности диагностикиunclassified
“…Несмотря на высокую чувствительность в определении патологической перестройки костной ткани при АШ, специфичность этого метода в среднем составляет 40-46% [23,24]. Сцинтиграфия с лейкоцитами, меченными 111Inоксином или 99m Tc-HMPAO (гексаметилпропиленамин), в сочетании с МРТ-томографией и рентгенологическими методами, а также позитронная эмиссионная томография (ПЭТ) с 18 F-фтордезоксиглюкозой ( 18 F-ФДГ) применяются преимущественно для улучшения дифференциального диагноза между артропатией и остеомиелитом [25][26][27][28]. Показано также, что сцинтиграфические признаки активности процесса достаточно хорошо коррелируют с динамикой температурного градиента, другими клиническими признаками АШ, а также с маркерами костного ремоделинга (например, с уровнем костной изоформы щелочной фосфатазы) [27,29].…”
Section: сахарный диабетunclassified